A STUDY ON EFFECT OF FINANCIAL AND NON-FINANCIAL INCENTIVES ON STAFF PRODUCTIVITY - Dingankar, Shreyas; Suryawanshi, Suresh; Behl, Gunjan; Kakde, Kirti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper aims to identify financial and non-financial incentives impacting the productivity of an employee in companies. The paper will discuss employees' productivity that affects the company’s performance and maintain a productive workforce. There is a strong bonding between incentive and productivity of an employee. The factors for improving employee productivity varies from industry to industry. Employees also gain a sense of purpose to work more efficiently when they work constructively, inspiring them to give their best. A study by Oxford faculty and the University of Oxford (named Employee Wellbeing, Productivity, and Firm Performance) found that employee inspiration was correlated with productivity and profitability, which on the whole affects employee loyalty.